Исследования квартала LX в западной части Херсонесского городища в 2009 г. - Бернацки, А.Б.; Кленина, Е.Ю. (Археологічні дослідження в Україні, 2010)
In the framework of a many-year scientific and research Ukrainian-Polish Project «Topography of Tauric Chersonesos » headed by Ye.Yu. Klyonina and A.B. Bernacki a study of the planning of the LX dwelling quarter dated from the 10th c. to the 14th c. was finished in 2009. This Late Byzantine quarter in the western part of Chersonesos city allows the authors to confirm a presumption about the existence of regular building up in this area until the desolation of the city in the end of the 14th c. — the beginning of the 15th c.